2021
DOI: 10.3390/plants10020249
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Somatic Embryogenesis and Cryopreservation of Agave tequilana Weber Cultivar ‘Chato’

Abstract: Agave tequilana Weber cultivar ‘Chato’ represents an important genetic supply of wild severely in decline populations of ‘Chato’ for breeding and transformation programs. In this work, the indirect somatic embryogenesis and cryopreservation of Somatic Embryos (SEs) were investigated using the ‘Chato’ cultivar as a study case. Methods: Embryogenic calli were induced by the cultivation of 1 cm of young leaves from in vitro plants on MS semisolid medium supplemented with 24.84, 33.13, 41.41, 49.69, and 57.98 μM 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
(61 reference statements)
0
2
0
1
Order By: Relevance
“…Previous studies have shown that the regrowth and conversion rates after cryopreservation were directly affected by the time of exposure to cryoprotectant treatment and the kind of cryoprotectant used. Delgado-Aceves et al [ 39 ] revealed that the regrowth and conversion of Agave somatic embryos achieved higher rates after exposure for 15 and 30 min in a plant vitrification solution (composed of glycerol, DMSO, ethylene glycol, and sucrose) when compared to exposures of 45 and 60 min, suggesting that lower incubation times in pretreatment solution may result in major recovery and conversion rates. Salaj et al [ 40 ] indicated that the regrowth rate after cryopreservation of ECs of different cell lines of P. nigra were affected by the pre-treatment used, in which sorbitol and maltose pre-treatment resulted in less regrowth than sucrose and cryopreservation did not affect the conversion and proliferation of cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the regrowth and conversion rates after cryopreservation were directly affected by the time of exposure to cryoprotectant treatment and the kind of cryoprotectant used. Delgado-Aceves et al [ 39 ] revealed that the regrowth and conversion of Agave somatic embryos achieved higher rates after exposure for 15 and 30 min in a plant vitrification solution (composed of glycerol, DMSO, ethylene glycol, and sucrose) when compared to exposures of 45 and 60 min, suggesting that lower incubation times in pretreatment solution may result in major recovery and conversion rates. Salaj et al [ 40 ] indicated that the regrowth rate after cryopreservation of ECs of different cell lines of P. nigra were affected by the pre-treatment used, in which sorbitol and maltose pre-treatment resulted in less regrowth than sucrose and cryopreservation did not affect the conversion and proliferation of cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also indicated that plant vitrification solutions are used in the cryoprotection process, and most previous studies also indicated that PVS2 was Sustainability 2023, 15, 14218 9 of 13 the best vitrification solution [15,51,52]. This is because it has a cryoprotection material that is not lethal to most plant tissues, and the most used and successful PVS2 concentration was 100% in different studies [15,[52][53][54]. Furthermore, the duration of incubation in PVS2 was documented in many studies as 30-50 min, and this was critical in many species [55].…”
Section: Cryopreservation Of S Dominica Callusmentioning
confidence: 99%
“…A histological analysis of the chronological sequence of morphological events during ontogeny is a way to know what morphogenic process was induced (Delporte et al, 2014). Somatic embryogenesis and/or organogenesis has been described and confirmed using histological analysis in different species (Delgado-Aceves et al, 2021;Mamgain et al, 2022;García-Hernández et al, 2022).…”
Section: Introductionmentioning
confidence: 99%